GESTÃO HOSPITALAR: SISTEMA DE INDICADORES E O PROGRAMA BRASILEIRO DE ACREDITAÇÃO - Neves Junior, Waldir Viana das (2004)
This paper identifies the use of the hospital accreditation provided by the Organização Nacional de Acreditação (National Organization of Accreditation) and the use of standard metrics as a tool for managing health service organizations, emphasizing the advantages that come out from adopting those methodologies. To do so, it was conducted a qualitative study, based upon interviews taken from people responsible for implementing such practices among 8 (eight) health service organizations (hospitals) in Brasil. The results show that the most part of the companies benefits from the use of those approaches, improving their physical infrastructures as well as operating and decision-making processes. Implementing those methodologies made it possible the development of practices of excellence and benchmarking, which provoked changes upon the entire companies, influencing positively customer satisfaction